Significance of Twist expression and its association with E-cadherin in esophageal squamous cell carcinoma - Sakamoto Akihiko (Journal of Experimental & Clinical Cancer Research, 2009)
Abstract Background Twist is a basic helix-loop-helix (bHLH) transcriptional factor that has been identified to play an important role in epithelial-mesenchymal transition (EMT)-mediated metastasis through the regulation of E-cadherin expression. However, few authors have examined the expression of Twist and E-cadherin and their prognostic value in patients with esophageal squamous cell carcinoma (ESCC). The purpose of this study is to evaluate the clinical significance of Twist and E-cadherin expression in ESCC. Methods We immunohistochemically investigated the relationship between their expression and clinicopathological factors including prognosis in surgical specimens of primary tumors in 166 patients with ESCC. Results The expression rate of high Twist was 42.0% and that of preserved E-cadherin was 40.4%. The expression of high Twist and reduced E-cadherin was significantly associated with depth of tumor invasion, lymph node metastasis, distant nodal metastasis, stage and lymphatic invasion, and poor prognosis. High Twist expression significantly correlated with reduced E-cadherin expression. In the preserved E-cadherin group, the 5-year survival rate was better for patients who were low for Twist expression than for those who were high for Twist expression. Multivariate analysis indicated that the combination of low Twist and preserved E-cadherin expression was an independent prognostic factor along with tumor depth, distant nodal metastasis and E-cadherin expression. Conclusions Evaluation of Twist and E-cadherin expressions should be useful for determining tumor properties, including prognosis, in patients with ESCC.